Nutritional Interventions for Cognitive Improvement in Children with ADHD and ASD: A Systematic Review from a Biomedical and Educational Standpoint - Kaczmarek, Marcelina; Dmowska , Dominika; Rymska, Karolina; Krzesimir Kuświk, Maciej; Chrzanowski, Dominik; Bajek, Wiktoria; Żmuda, Kinga; Lewandowski, Mikołaj (Journal of Education, Health and Sport, 2026)
Background. ADHD and ASD are complex neurodevelopmental disorders characterized by oxidative stress and gut-brain axis dysfunction. Lifestyle factors, especially nutrition, are key modifiable elements affecting brain plasticity. Aim. To analyze the impact of dietary interventions and supplementation on cognitive functions and behavior in children with ASD and ADHD. Material and methods. A systematic review of literature (2020–2024) was conducted using the PubMed database, including RCTs, meta-analyses, and reviews. Results. Oligoantigenic diets effectively reduce core symptoms. Supplementation with omega-3, vitamin D, and magnesium correlates with improved neurocognition. Microbiome modulation via probiotics benefits mental health and sleep. Conclusions. Nutritional interventions serve as valuable support for pharmacological and educational therapies, impacting learning effectiveness.